2015
DOI: 10.1371/journal.pone.0128890
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Brain Microvascular Endothelial-Like Cells from Human Induced Pluripotent Stem Cells by Co-Culture with C6 Glioma Cells

Abstract: The blood brain barrier (BBB) is formed by brain microvascular endothelial cells (BMECs) and tightly regulates the transport of molecules from blood to neural tissues. In vitro BBB models from human pluripotent stem cell (PSCs)-derived BMECs would be useful not only for the research on the BBB development and function but also for drug-screening for neurological diseases. However, little is known about the differentiation of human PSCs to BMECs. In the present study, human induced PSCs (iPSCs) were differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 27 publications
7
41
0
Order By: Relevance
“…This was further verified by detecting claudin, occludin, and ZO-1 expression, as well as by observing vascular-like structures in Matrigel Ò and uptake of acetylated low-density lipoprotein [52]. However, these cells alone yielded a TEER of only 55 Ocm 2 , indicating a barrier tightness that is far from representative of the in vivo BMEC [52]. This indicated that induction by co-culturing with neural cultures is not sufficient for inducing BMEC properties, possibly due to the importance of factors secreted and/or mechanical interactions that pericytes and astrocytes have on BMECs.…”
Section: Psc Differentiation Into Nvu Cell Typesmentioning
confidence: 70%
See 2 more Smart Citations
“…This was further verified by detecting claudin, occludin, and ZO-1 expression, as well as by observing vascular-like structures in Matrigel Ò and uptake of acetylated low-density lipoprotein [52]. However, these cells alone yielded a TEER of only 55 Ocm 2 , indicating a barrier tightness that is far from representative of the in vivo BMEC [52]. This indicated that induction by co-culturing with neural cultures is not sufficient for inducing BMEC properties, possibly due to the importance of factors secreted and/or mechanical interactions that pericytes and astrocytes have on BMECs.…”
Section: Psc Differentiation Into Nvu Cell Typesmentioning
confidence: 70%
“…The study by Minami et al on co-culturing with a glioma cell line used CD34 and CD144 (VE-cadherin) as markers for ECs, which were sorted from the population and analyzed for CD31 (PECAM) and Von Willebrand factor to identify BMECs. This was further verified by detecting claudin, occludin, and ZO-1 expression, as well as by observing vascular-like structures in Matrigel Ò and uptake of acetylated low-density lipoprotein [52]. However, these cells alone yielded a TEER of only 55 Ocm 2 , indicating a barrier tightness that is far from representative of the in vivo BMEC [52].…”
Section: Psc Differentiation Into Nvu Cell Typesmentioning
confidence: 77%
See 1 more Smart Citation
“…19,57 Current in vitro BBB models are usually based on commercially available plastic and porous transwell membranes. In this study, we designed and 3D-printed a holder that can support an electrospun PLGA mesh and can perfectly fit into the transwell insert.…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition, hiPSC-ECs cocultured with primary rat astrocytes or C6 rat glioma cells also showed brain EC phenotypes. 20,57 A hallmark of the BBB is a high TEER because of the tight junctions between ECs to maintain barrier integrity. In the current study, although the TEER value was lower than the native BBB (~1000–2000 Ω·cm 2 ), 10,12 it is still within the reported range for in vitro BBB models.…”
Section: Discussionmentioning
confidence: 99%